Keynes's theories of the business cycle: Evolution and contemporary relevance - Pablo G. Bortz (Levy Economics Institute of Bard College, 2021)
This paper traces the evolution of John Maynard Keynes's theory of the business cycle from his early writings in 1913 to his policy prescriptions for the control of fluctuations in the early 1940s. The paper identifies six different "theories" of business fluctuations. With different theoretical frameworks in a 30-year span, the driver of fluctuations- namely cyclical changes in expectations about future returns-remained substantially the same. The banking system also played a pivotal role throughout the different versions, by financing and influencing the behavior of return expectations. There are four major changes in the evolution of Keynes's business cycle theories: a) the saving- investment framework to understand changes in economic fluctuations; b) the capabilities of the banking system to moderate the business cycle; c) the effectiveness of monetary policy to fine tune the business cycle through the control of the short-term interest rate or credit conditions; and d) the role of a comprehensive fiscal policy and investment policy to attenuate fluctuations. Finally, some conclusions are drawn about the present relevance of the policy mix Keynes promoted for ensuring macroeconomic stability.
Keywords: B31; E12; E32; E44; E63; 330; John Maynard Keynes; Business Cycle; Fiscal Policy; MonetaryPolicy; Financial System; Uncertainty